Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Setiajaya Mobilindo Depok - latifa, lulu; kamil, musthafa (Jurnal Bintang Manajemen, 2024)
This research aims to describe motivation and work discipline on employee performance at PT. Setiajaya Mobilindo Depok. Motivation and work discipline play an important role in improving employee performance. Because with motivation, employees will be motivated to increase their energy and thoughts in realizing the achievement of company goals. Providing motivation will influence the level of work discipline aimed at achieving optimal performance. This research uses a quantitative approach with a causal associative type of research. The population was 58 employees and the sample used was a saturated sample. The data collection technique uses a questionnaire. Data processing uses the SPSS version 25 program with multiple linear regression analysis techniques. Based on the research results, it is known that 1) the motivation variable partially has a positive and significant effect on the performance of PT employees. Setiajaya Mobilindo Depok. 2) The work discipline variable partially has a positive and significant effect on the performance of PT employees. Setiajaya Mobilindo Depok. Meanwhile 3) simultaneously motivation and work discipline have a positive and significant effect on the performance of PT employees. Setiajaya Mobilindo Depok.